Appeasement reconsidered investigating the mythology of the 1930s - Record, Jeffrey (Strategic Studies Institute, U.S. Army War College, 2005)
U.S. use of force since 1945 has been significantly influenced by the perceived consequences of appeasing Hitler in the 1930s, and from the mid-1970s to 2001 by the chilling effect of the Vietnam War. As the United States approached its second war with Iraq, proponents cited the Munich analogy to justify the war, whereas opponents argued that the United States was risking another Vietnam. Though reasoning by historical analogies is inherently dangerous, an examination of the threat parallels between Hitler and Saddam Hussein, and between the Vietnam War and the situation the United States has confronted in post-Baathist Iraq, reveals that the Munich analogy was misused as an argument for war, whereas the American dilemma in Iraq bears some important analogies to the Vietnam conflict, especially with respect to the challenges of state-building and sustaining domestic public support for an unpopular protracted war.
"August 2005."
Includes bibliographical references (p. 46-54)
Keywords: Munich Four-Power Agreement -- (1938); Weltkrieg (1939-1945); World War, 1939-1945 -- Diplomatic history; World War, 1939-1945 -- Causes